2014
DOI: 10.15352/bjma/1396640052
|View full text |Cite
|
Sign up to set email alerts
|

The controlled separable complementation property and monolithic compacta

Abstract: For a compact K, a necessary condition for C(K) to have the Controlled Separable Complementation Property is that K be monolithic. In this paper, we prove that when K contains no copy of [0, ω ω ] and the set of points which admit a countable neighborhood base is a cofinite subset of K, then monolithicity of K is sufficient for C(K) to enjoy the Controlled Separable Complementation Property. We also show that, for this type of compacta K, the space C(K) is separably extensible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Note that Proposition 2.9 provides an example of a space with the SCP but not the c 0 EP. A stronger property than the SCP is the controlled separable complementation property (CSCP) that was introduced in [26] and studied in a series of papers [11,12,13]. A surprising consequence of Theorem 2.5 is that the CSCP implies the c 0 EP.…”
Section: (Ii) Absconv(a)mentioning
confidence: 99%
“…Note that Proposition 2.9 provides an example of a space with the SCP but not the c 0 EP. A stronger property than the SCP is the controlled separable complementation property (CSCP) that was introduced in [26] and studied in a series of papers [11,12,13]. A surprising consequence of Theorem 2.5 is that the CSCP implies the c 0 EP.…”
Section: (Ii) Absconv(a)mentioning
confidence: 99%
“…& Wójtowicz, M., 2011;Ferrer, J., Koszmider, P. & W. Kubiś, 2013;Ferrer, J., 2014;Ferrer, J., 2009), we studied the controlled version of the separable complementation property (CS CP, for short) for general Banach spaces and in particular for C(K A ) spaces when K A is the Mrówka compact associated to an almost disjoint family A of countable subsets of a given set. After seeing that K being monolithic, see (Arkhangel'skii, A. V., 1992), is a necessary condition in order that the space C(K) enjoys the CS CP, we proved this condition to be sufficient when K is a Mrówka compact and moreover we also showed that this condition suffices in general when K is a scattered compact such that each of its points, except possibly the ones in the top layer, admit a countable neighborhood base.…”
Section: Introductionmentioning
confidence: 99%
“…Note that Proposition 2.8 provides an example of a space with the SCP but not the c 0 EP. A stronger property than the SCP is the controlled separable complementation property (CSCP) that was introduced in [26] and studied in a series of papers [12,11,13]. A surprising consequence of Theorem 2.5 is that the CSCP implies the c 0 EP.…”
mentioning
confidence: 99%